Challenges and Prospects of Integrating Artificial Intelligence Technology in the Implementation of Law No. 17 of 2023 on Health: A Legal and Medical Practice Perspective - Islami, Sonia Ayu; Harisi, Rusmina; Fikri, Ahmad Ma'mun (Golden Ratio of Law and Social Policy Review, 2025)
This study explores the challenges and prospects of integrating artificial intelligence (AI) technology into the implementation of Indonesia’s Law No. 17 of 2023 on Health, from both legal and medical practice perspectives. Although the law represents a significant effort to modernize healthcare regulations in line with global developments, it has been criticized for being drafted hastily and for its lack of attention to emerging technologies such as AI. Similarly, Government Regulation (PP) No. 28 of 2024, which serves as an implementing regulation of Law No. 17 of 2023, provides little clarification regarding AI-related provisions. The study identifies several major challenges in AI adoption, including regulatory and legal constraints, technical and infrastructural limitations, and ethical and data privacy concerns. Conversely, the prospects of AI integration within the health sector include potential gains in efficiency and diagnostic accuracy, innovations in HealthCare delivery, and increased support from both governmental and private sectors. Furthermore, insights from legal practitioners and medical professionals are analyzed to present a holistic understanding of AI implementation in Indonesia’s healthcare system. The findings suggest that AI holds substantial potential to transform Indonesia’s healthcare sector; however, its success depends on the establishment of a specific, comprehensive, and adaptive regulatory framework. Accordingly, this study recommends the formulation of supportive policies and regulations, strategies to address existing barriers, and directions for future research on AI in healthcare.